Development of electrical properties in lead-free bismuth sodium lanthanum titanate-barium titanate ceramic near the morphotropic phase boundary - Jarupoom P. (2014)
The near morphotropic phase boundary (MPB) of lead-free piezoelectric ceramics based on bismuth sodium lanthanum titanate (Bi0.487Na0.487La0.017TiO3:BNLT) and barium titanate (BaTiO3:BT) was carefully investigated by a modified two step mixed-oxide method. In this case the BNLT and BT powders were produced separately using calcination temperatures of 900 °C and 1200 °C, respectively. After that they were mixed with the desired compositions of (1 - x)BNLT-xBT, where x = 0.00, 0.02, 0.04, 0.06, 0.08, and 0.10. Then the powders were pressed and subsequently sintered at various temperatures to obtain the maximum density under each condition. It was found that the BT addition has a significant effect on grain growth inhibition of the BNLT-BT ceramics and this in turn gave rise to an enhancement in dielectric constant (εr) of the corresponding ceramics. The piezoelectric coefficient (d33) was also improved greatly to about 130 pC/N in the 0.96BNLT-0.04BT ceramic sample sintered at 1125 °C. This offered an opportunity to obtain a good candidate for replacing the lead-based piezoelectrics. © 2007 Elsevier B.V. All rights reserved.